School performance in youth after a concussion - DeMatteo, Carol A.; Jakubowski, Josephine; Randall, Sarah; Stazyk, Kathy; Lin, Chia-Yu; Yakubov, Rebecca (Frontiers in Sports and Active Living, 2022)
Objective This study aimed to identify school problems and levels of cognitive activity in youths aged 5–18 years with a concussion during the recovery stages of return to school (RTS). Study Design In a prospective cohort, participants completed in-person assessments at three time points: First Visit Post-injury, Symptom Resolution Visit, and Follow-Up Visit. These time points varied based on the participants’ recovery progress. The post-concussion symptom scale (PCSS) and a cognitive activity scale were completed every 2 days until symptom resolution was achieved. Participants and their parents completed a school questionnaire detailing how their concussion had impacted their school learning/performance and their level of concern about their injury as well as the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT). Results Sixty-three percent (N = 44/70) of participants returned to school by the First Visit Post-injury (average 7.7 days following injury), and of these, 50% (N = 22) were experiencing school problems. Sixty-five participants (out of 70) returned to school at the Follow-Up Visit, and of these, 18% reported school problems. There was a significant difference in the school problems reported by parents and youth. At the First Visit Post-injury, the youth reported more problems (p = 0.02), and the In-Person Symptom Resolution Visit with parents reported more problems (p = 0.01). The cognitive activity score increased, while the PCSS score decreased from RTS Stage 1 to Stage 5. Conclusions This study identified that 50% of youth experienced school problems at the First Visit Post-injury, whereas only 18% reported school problems at the Follow-Up Visit. There is a significant difference in the perception of school problems reported by youth and their parents at different stages of recovery. The amount and complexity of cognitive activity increased with decreasing symptoms and increasing RTS stage. Findings can guide youth with a concussion and their parents in supporting a cautious return to school with accommodations. Healthcare providers and researchers can use this knowledge to better support youth in their return to school and understand the importance of gathering information from youth and their parents to gain the best insight into recovery.